2004
DOI: 10.1007/s00109-004-0574-8
|View full text |Cite
|
Sign up to set email alerts
|

Renal function in relation to three candidate genes in a Chinese population

Abstract: We recently found in a white population that the genes encoding angiotensin-converting enzyme (ACE, I/D polymorphism), a-adducin (Gly460Trp), and aldosterone synthase ( 344C/T) jointly influence renal function. We therefore investigated in a Chinese population the associations between the serum concentrations of creatinine and uric acid and these three genetic polymorphisms. We genotyped 471 ethnic Han Chinese subjects from 125 nuclear families recruited in northern China via random population sampling (75%) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
3
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
2
3
0
Order By: Relevance
“…For the distribution of the ACE I/D polymorphism, the D allele frequency of the Koreans in the present study (39.6%) was much lower than that of African Americans (63%) 11 and Caucasians (64%), 39 but was higher than that of Australian Aborigines (12.6%) 40 and Amerindians (26.5%), 41 and similar to those described for Chinese Han (38%) 42 and mainland Japanese populations (40%). 17 Several reports have shown that ACE I/D polymorphism accounts for half of the variance of plasma ACE levels in the RAAS pathway.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…For the distribution of the ACE I/D polymorphism, the D allele frequency of the Koreans in the present study (39.6%) was much lower than that of African Americans (63%) 11 and Caucasians (64%), 39 but was higher than that of Australian Aborigines (12.6%) 40 and Amerindians (26.5%), 41 and similar to those described for Chinese Han (38%) 42 and mainland Japanese populations (40%). 17 Several reports have shown that ACE I/D polymorphism accounts for half of the variance of plasma ACE levels in the RAAS pathway.…”
Section: Discussionsupporting
confidence: 82%
“…14 Therefore, because AT-II receptors are typical G-protein-coupled receptors, it is very likely that D allele associated with elevated ACE concentrations may prove to be pathophysiological in individuals whose genetic structure is composed of an allelic variant that causes increased cellular responsiveness. 42 Thus, the GNB3 825T allele is an important marker to study for interactions with the ACE D allele.…”
Section: Discussionmentioning
confidence: 99%
“…Use of a prospective design in a cohort protects against confounding by population stratification. Furthermore, our prospective epidemiological results corroborate a hypothesis independently raised by studies in never-treated hypertensive patients, 11,12 previous population surveys, [13][14][15][16] and pharmacogenomic studies, 32,33 and they are supported by animal experiments 26 and an established pathogenetic mechanism. 9,10 Moreover, we replicated our initial findings in human fibroblasts in kidney cells of human origin transfected by the wild-type and mutated human ADD1.…”
Section: Discussionsupporting
confidence: 86%
“…9 Substitution of glycine by tryptophan in the cytoskeleton protein ␣-adducin (ADD1 Gly460Trp) enhances tubular sodium reabsorption in the kidney. 9,10 Studies of never-treated hypertensive patients 11,12 and European [13][14][15] and Chinese populations 16 suggested that cardiovascular risk factors are associated with the ACE D allele, but only in the presence of mutated ADD1. Here, we report the results of a prospective population study and cell experiments, which further clarify the interaction between these 2 polymorphisms from a prognostic and mechanistic point of view.…”
mentioning
confidence: 99%
“…However, we adjusted for alcohol intake in our models to assess the relation between increased uric acid concentrations and incident hypertension. Recently, it has been shown that uric acid is positively associated with the gene encoding angiotensin-converting enzyme (ACE, I/D polymorphism) in a Chinese population (36,37 ). Thus, we could not exclude the possibility that genetic variants may contribute to the association between uric acid and the risk of developing hypertension.…”
Section: Discussionmentioning
confidence: 96%